2012
DOI: 10.1186/1475-2840-11-101
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of surrogate markers of atherosclerosis in low to intermediate risk patients with Type 2 Diabetes

Abstract: BackgroundType 2 diabetes mellitus (T2DM) patients are at increased risk of developing cardiovascular events. Unfortunately traditional risk assessment scores, including the Framingham Risk Score (FRS), have only modest accuracy in cardiovascular risk prediction in these patients.MethodsWe sought to determine the prognostic values of different non-invasive markers of atherosclerosis, including brachial artery endothelial function, carotid artery atheroma burden, ankle-brachial index, arterial stiffness and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…As a whole, our findings support the recommendation that the ABI should be more widely used in the routine clinical management of individuals with type 2 diabetes, not only in those with signs or symptoms suggesting PAD, as currently recommended. Some previous longitudinal studies in individuals with type 2 diabetes [20][21][22][23][24][25][26][27][28] and in individuals with and without diabetes [14][15][16][17] have reported that the ABI is a risk marker for future CVE occurrence and mortality, whereas other studies have contradicted this finding [11-13, 18, 19]. Our findings corroborate the studies reporting positive results.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As a whole, our findings support the recommendation that the ABI should be more widely used in the routine clinical management of individuals with type 2 diabetes, not only in those with signs or symptoms suggesting PAD, as currently recommended. Some previous longitudinal studies in individuals with type 2 diabetes [20][21][22][23][24][25][26][27][28] and in individuals with and without diabetes [14][15][16][17] have reported that the ABI is a risk marker for future CVE occurrence and mortality, whereas other studies have contradicted this finding [11-13, 18, 19]. Our findings corroborate the studies reporting positive results.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, some previous studies have demonstrated a lack of prognostic value for the ABI in diabetic individuals in contrast to non-diabetic individuals [11][12][13], although others have reported similar positive predictive performances in diabetic and non-diabetic individuals [14][15][16][17]. Similarly, conflicting results regarding the prognostic value of the ABI have been reported by cohort studies comprised exclusively of individuals with type 2 diabetes, with some studies negating [18,19] and others demonstrating [20][21][22][23][24][25][26][27][28] its importance. Moreover, some of the positive studies [24,25,27,28] assessed whether the ABI, beyond being a risk marker, was also capable of improving risk stratification for adverse outcomes, with contradictory findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, although some clinical measurements were different between two groups’ comparisons in the present study, no obvious relationship was found with the arterial stiffness changes by the statistical correlation analysis, further analyze the data with adjustment was not performed as other studies did [28,29]. Thirdly, considering the fact that the number of subjects with the presence of plaque was not sufficient for quantitative statistical analysis, the value of plaque score [30] was not evaluated in this study.…”
Section: Discussionmentioning
confidence: 61%
“…The leukocyte count has been reported to correlate with coronary heart disease (CHD) since 1920s [2]. In addition, many epidemiologic studies have reported that an increased leukocyte count is a strong and independent risk factor for cardiovascular events [3][4][5][6][7][8][9][10] and for the prevalence and progression of subclinical carotid atherosclerosis [11][12][13][14][15][16], suggesting that leukocyte count is useful as a clinical marker to predict atherosclerotic diseases. On the other hand, leukocyte count includes several types of cells which have different participation form in atherogenesis.…”
Section: Introductionmentioning
confidence: 99%